Spatial and Temporal Variability of Phosphates, Nitrates and Selected Physico-Chemical Parameters of River Nzoia - Tarus, S. J.; Kituyi , J. L.; Segor, F. K. (Africa Environmental Review Journal, 2022)
Several agricultural activities are practiced within the River Nzoia catchment area, most of which involve application of chemicals in form of fertilisers and pesticides. Most of these chemicals end up in the river in form of phosphates and nitrates, thus affecting the aquatic life of the river. Spatial and temporal variability of major pollutant loads of the River Nzoia has been determined with a view of assessing the safety of river. This study reports the current contaminant loads determined in River Nzoia catchment area, which were; nitrates (NO3-N) and phosphates (PO4-P), the physico-chemical parameters; pH, temperature, conductivity, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD) and total dissolved solids (TDS). All these were tested in the three matrices; the soil, sediments and water. The stratified samples were collected from eight (8) different sites from Kitale down to Mumias in the River Nzoia in both the dry and wet seasons. The samples were then digested by the wet method and analyzed for nitrates and phosphates using the colorimetric technique. Titrimetric method was used for COD analysis while the DO meter was used to measure the BOD based on incubation. TDS was analyzed using the evaporation vs weight change method. pH, temperature, conductivity and DO were determined in situ using respective meters. Collected data were analysed descriptively using MS Excel spreadsheets and statistical package for social science (SPSS) version 20. Comparison for variations between the sampling sites was done using one way ANOVA. Levels of nitrates in water were found to be higher than the maximum permissible levels in water samples from Cherangani [12.30 ± 0.05 mg/L], Moi’s Bridge [14.4±1.15 mg/L], Pan-Paper [17.2 ± 0.15 mg/L] and Mumias [15.3 ± 0.35 mg/L]. However, phosphates, temperature, DO, BOD, conductivity and TDS were within permissible limits in all the sites while COD [51.0 ± 13.7 mg/L] at Mumias site was found to be relatively above the recommended limit. There seems to be an accumulation of some pollutants in River Nzoia as it progresses towards Lake Victoria. Therefore, control measures should be taken within the catchment area to avoid the river manifesting serious environmental pollution.